TELAAH HARTA DALAM PERSPEKTIF AL-QUR’AN: AMANAH DAN TANGGUNG JAWAB SOSIAL - Sumadi, Eko Sumardianto (LPPM STAI Muhammadiyah Probolinggo, 2025)
In Islamic perspective, wealth is regarded as a trust (amanah) from Allah, carrying both spiritual and social responsibilities. This study aims to examine the concept of wealth in the Qur’an, including the principles of fair wealth management, the quality of wealth eligible for charity, and the equitable distribution of wealth to achieve social welfare. A qualitative approach utilizing a literature review method is employed, analyzing Qur’anic verses, hadiths, and references from classical and contemporary tafsir. The findings reveal that Islam emphasizes the significance of halal and quality wealth in charity as a manifestation of social responsibility. The principle of justice in wealth distribution is realized through mechanisms such as zakat, infak, and waqf, which aim to prevent wealth concentration and social inequality. Moreover, Islam promotes responsible wealth management that addresses not only individual needs but also contributes to societal balance and harmony. In the modern context, this study identifies global challenges such as capitalism, economic disparity, and digitalization that influence the application of Shariah-based wealth management. Nevertheless, innovations such as zakat digitalization and modern waqf management provide practical solutions to enhance the effectiveness of wealth redistribution. These findings underscore the adaptability of Islamic principles in addressing contemporary challenges while remaining firmly rooted in Qur’anic and Sunnah values. This research offers a significant contribution to the study of Islamic economics by providing a comprehensive understanding of wealth as a trust. The findings are expected to serve as a foundation for developing a Shariah-compliant economic system that is equitable, sustainable, and relevant to the demands of a global society.